IDENTIFIKASI DAN UJI AKTIVITAS ANTIBAKTERI KAPANG LAUT DIISOLASI DARI KORAL LUNAK FAVITES SP. - Ahmad Zainal Fanani; Tisa Ayu Novitasari; Siti Choiriah Rofi’ah; Siti Nur Rukhoiyah Dewi; Heru Pramono (Universitas Medan Area, 2019)
The aims of this study was to investigate the antimicrobial activity of fungi associated with coral. The fungi was cultured by streak plate method on potato dextrose agar (PDA) and reisolated with the same medium and were stored in slant agar for identified with morphological approach. Antibacterial activity fungi associated with coral was tested using overlay method against Escherichia coli and Staphylococcus aureus. Based on morphological analysis, five fungi were identified as Candidasp., Fusariumsp., Cladophialophorasp., Phaeoacremoniumsp., and Trichophytonsp. The antibacterial assay showed that Phaeoacremoniumsp. and Trichophytonsp. has antibacterial activity and potential as source of antibacterial for futher study.